Reversing the slide : a strategic guide to turnarounds and corporate renewal - Shein, James B., 1942- (San Francisco : Jossey-Bass, 2011)
'A just-in-time guide for revamping distressed companies Drawn from the author's decades of experience advising, purchasing, and reviving distressed companies across industries, geographies, and sizes, Reversing the Slide is designed to help help executives, managers, and employees revitalize downtrodden companies. It shows how to: the stage of distress; select the tactics appropriate for each stage; understand the use of entrepreneurial concepts; avoid pitfalls common to turnarounds; determine the legal, financial, strategic, and operational steps in the process; discover why the principal of'ready, fire, aim' should guide the decision-making process in situations with time pressure and significant uncertainty; and uncover the secrets of effective leadership and governance. Contains step-by-step instructions for helping troubled organizations bounce back with vigor. Often quoted in the Wall Street Journal, the author is an authority on restructuring and downsizing. Offers a handbook for implementing a successful corporate turnaround. Shein's insightful advice on what works, what does not, and why it will prove invaluable to executives, managers, and employees in helping troubled companies before it's too late.'--
Machine generated contents note: Box 1: Typical Covenants Tripped by Downturns -- Box 2: The Effects of Financial Shenanigans -- Box 3: Governance and Leadership Issues in Family-Owned Businesses -- Box 4: Other Legal Issues in Announcing Layoffs -- Box 5: State Laws -- Box 6: DIP Financing -- Box 7: Committee Formation -- Box 8: Plan Confirmation -- Box 9: Chapter 9 Bankruptcy -- Box 10: Additional Issues in Valuing Distressed Companies -- Box 11: Fiduciary Duties of Directors in M&A Transactions.
Includes bibliographical references and index.
Keywords: Corporate turnarounds -- United States -- Management; Corporate turnarounds -- United States -- Case studies; Working capital -- United States; Strategic planning -- United States